Analysis of Remaining Project Cost Estimate Temporary Schedule (ETS) & Final Project Time Estimate All Schedule (EAS) - Saputra, Edwin Octavianto; Muhammadun, Haris; Marleno, Risma (International Journal of Social Science and Community Service, 2024)
The wheat silo and pellet silo structure repair project phase 3 by PT ISM Bogasari Surabaya is an annual infrastructure maintenance and strengthening activity aimed at supporting the smooth production process. Therefore, it is crucial to complete the project on time according to the contract to proceed to the next stage of repair and avoid delays that could result in cost overruns. This study uses Earned Value Method (EVM) analysis to address these issues and assess the performance of costs and implementation time as the project progresses. The indicators used in the analysis include the calculation of Estimated To Complete (ETC) and Estimated At Complete (EAC) for forecasting project completion costs, and Estimated Temporary Schedule (ETS) and Estimated All Schedule (EAS) for forecasting project completion time. Based on the results of the cost and time performance analysis, the EAC value is 0.77% smaller, which is Rp. 21,825,605,678, compared to the contract value. The time to complete the EAS project is 481 days, with an addition of 26 days, resulting in a 0.6% longer project completion time.